The Allemann collection from the Santa Cruz Formation (late early Miocene), Argentina, in Zurich, Switzerland - Zurita Altamirano, Daniel (2019)
One of the best-known faunal assemblages that characterizes the past ecosystems from South America comes from the Santa Cruz Formation in Argentina. This assemblage is formed by an endemic fauna, which included ground sloths, glyptodonts, native ungulates, terror birds (phorusrhacids), among others. The Santacrucian South American Land Mammal Age is dated 18.0–15.6 Ma, late early Miocene. Current curatorial efforts revealed a large collection of over 1100 fossil remains from the Santa Cruz Formation, donated in 2007 to the Paleontological Museum, University of Zurich, Switzerland. The fossils were brought to Switzerland in the late 1880s by Theodor Allemann, an engineer and amateur collector. The collection includes skulls, isolated teeth, mandibles, and isolated postcranial elements. Postcranials are mainly represented by astragali, calcanei, and osteoderms. The study of the remains allowed us to recognize 20 families of mammals, one of birds, and one of amphibians: Abderitidae, Palaeothentidae (Paucituberculata); Hathliacynidae (Sparassodonta); Dasypodidae, Peltephilidae, and Glyptodontidae (Cingulata); Megatheriidae and Megalonychidae (Tardigrada); Astrapotheriidae (Astrapotheria), Protherotheriidae and Macraucheniidae (Litopterna); Toxodontidae, Homalodotheriidae, Hegetotheriidae and Interatheriidae (Notoungulata); Dasyproctidae, Dinomyidae, Neoepiblemidae, Chinchillidae, Erethizontidae, Echimyidae and Eocardidae (Rodentia); Phorusrhacidae (Cariamiformes); and Calyptocephalellidae (Anura). Among them, we identified 28 genera and 9 species. Reference to the previous work on the Santa Cruz fauna and the good preservation of the material allow us to achieve taxonomic resolution in the identifications. We discuss the potential usefulness of this collection for studying the paleobiology of specimens/species of this fauna.